2004
DOI: 10.3748/wjg.v10.i7.1069
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 3020insC frameshift mutation is not associated with inflammatory bowel disease in Chinese patients of Han nationality

Abstract: NOD2 gene 3020insC frameshift mutation is not a major contributor to the susceptibility to both Crohn's disease and ulcerative colitis in Chinese Han patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 14 publications
3
56
1
1
Order By: Relevance
“…The candidate gene study shows that the NOD2 variants statistically and functionally confirmed in Europeans are completely absent -both in patients and controlsin the Japanese population (Yamazaki et al 2002). This result is consistent with the other East Asian populations, such as Korean (Croucher et al 2003) and Chinese (Guo et al 2004). To elucidate the similarities and differences of susceptibility to IBD between Europeans and the Japanese, associations with CD and UC have been tested for seven susceptible genomic regions, including NOD2, IL23R, ATG16L1, TNFSF15, SLC22A4, IRGM, and 10q21 (Nakagome et al 2010).…”
Section: Genetic Studies Of Ibd In Japanese ("Non-european-ancestry")supporting
confidence: 77%
“…The candidate gene study shows that the NOD2 variants statistically and functionally confirmed in Europeans are completely absent -both in patients and controlsin the Japanese population (Yamazaki et al 2002). This result is consistent with the other East Asian populations, such as Korean (Croucher et al 2003) and Chinese (Guo et al 2004). To elucidate the similarities and differences of susceptibility to IBD between Europeans and the Japanese, associations with CD and UC have been tested for seven susceptible genomic regions, including NOD2, IL23R, ATG16L1, TNFSF15, SLC22A4, IRGM, and 10q21 (Nakagome et al 2010).…”
Section: Genetic Studies Of Ibd In Japanese ("Non-european-ancestry")supporting
confidence: 77%
“…6 In the Asian cohorts studied, NOD2 variants are rare and do not contribute to Crohn's disease, suggesting ethnic heterogeneity in disease predisposition. [7][8][9] In Europe, the disease susceptibility caused by the R702W, G908R and 3020insC variants appears less prominent in Finland, Sweden, Iceland, Scotland and Ireland, than in other populations. 1,3,4,10,11 For instance, in Scotland and Ireland the population-attributable risk of the 3 common NOD2 variants is estimated to be only a third of that in other Caucasian populations.…”
mentioning
confidence: 99%
“…Genetic variation of NOD2 has been shown to associate with increased susceptibility to Crohn's disease in several independent studies, although in some populations no association has been observed (1)(2)(3)(4)(5)(6)(7)(8)(9). Three common mutations, two missense changes (Arg702Trp and Gly908Arg) and one frameshift change (3020insC31007fs), located in the leucinerich repeat (LRR) domain of the NOD2 protein have been reported to be linked with the disease (1,4).…”
Section: Introductionmentioning
confidence: 99%